From phosphine-promoted to phosphine-catalyzed reactions by in situ phosphine oxide reduction. Issue 40 (5th October 2016) - Voituriez, Arnaud; Saleh, Nidal
Graphical abstract: Highlights: Through this digest, we will summarize results on newly developed phosphine-catalyzed reactions. Catalytic Wittig, Mitsunobu, Staudinger, Appel reactions, and others. In situ chemoselective phosphine oxide reduction. Abstract: The well-known stoichiometric phosphine-promoted reactions such as the Wittig, Mitsunobu, Staudinger, Appel reactions, and others are widely used in organic chemistry. Recently, many efforts have been made to render these reactions catalytic in phosphine. Besides decreasing wastes, these catalytic reactions have the advantage to facilitate the purification of the products. The regeneration of the active catalyst was possible by means of reagents that reduce in situ the phosphine oxide formed during the reaction. Through this digest, we will summarize results on newly developed phosphine-catalyzed reactions.